The effects of globalization on firm performance / Zarrith Natasha Mohammad Tapsir - Mohammad Tapsir, Zarrith Natasha (Faculty of Business and Management, 2018)
Globalization challenges firms to become more efficient and well – organized while simultaneously extending the geographical reach of their operations. The purpose of this research study is to investigate the effects of globalization on firm performance among multinational corporations (MNCs) that are headquartered in Malaysia and outside Malaysia. Such effects were global market opportunities, global competitive threats and global market uncertainty. This research is a quantitative research which the instrument for the data collection used is the self-administered electronic questionnaires. A survey design was adopted and data was collected at a percentage of 54% from the total of 280 respondents that act as a sample size from the population of 1050 companies. Simple random sampling technique has been used as a sampling technique. The data collected then to key in using Statistical Package for the Social Science (SPSS) Version 20 Software. Several analyses have been done by using the SPSS such as reliability analysis, frequency distribution, descriptive analysis, correlation analysis and multiple regression. The results of the analyses provide considerable support for literature arguing that globalization acts as a two-edged sword which it can be beneficial and detrimental to business. Therefore, all organizations should take cognizance on global market opportunities while carefully managing its threats in order to be succeeded in today’s global arena.